2014
DOI: 10.1051/matecconf/20141408001
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the grain structure of IN718 during selective electron beam melting

Abstract: Abstract. Selective electron beam melting (SEBM) is an additive manufacturing method where complex parts are built from metal powders in layers of about 50 µm. SEBM works under vacuum conditions which results in a perfect protection of the metal alloy. The electron beam is used for heating (about 900 • C building temperature) and selective melting. The high beam velocities allow innovative scanning strategies in order to adapt the local solidification conditions which determine the epitaxial solidification pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 14 publications
4
63
0
1
Order By: Relevance
“…(9) and (12). The calculated values of the temperature gradient and the cooling rate are then filtered along the whole transient liquidus isotherm, to understand the variations along the liquidsolid interface as the solidification proceeds.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(9) and (12). The calculated values of the temperature gradient and the cooling rate are then filtered along the whole transient liquidus isotherm, to understand the variations along the liquidsolid interface as the solidification proceeds.…”
Section: Results and Analysismentioning
confidence: 99%
“…K€ orner et al [9] shown the possibility of obtaining both epitaxial and near equiaxed grains in different layers by varying the scan strategy and beam parameters between the layers. Dehoff et al [10] experimentally demonstrated the feasibility of producing highly misoriented equiaxed grains and oriented columnar grains in the same layer by rapidly changing the scan strategy between line and point heat sources.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the major EBM Ni-base superalloy research is focus on IN718 [53,[74][75][76][77][78] and IN625 [79,80] because of their weldabilities. However, the relatively high chamber temperature during process enables the possibility of manufacturing those γ ′ strengthened Ni-based superalloy.…”
Section: Materials Manufactured With Ebmmentioning
confidence: 99%
“…Efforts have also been put in identifying process-microstructure relationship, showing that besides the higher density and better surface finish, the controlled tailoring of grain structures and crystallographic textures can be achieved by adjusting the scan strategies [62,76,78,189,190].…”
Section: Ebm In718mentioning
confidence: 99%
“…Andreas Kergaßner 1, * , Julia Mergheim 1 , and Paul Steinmann 1 1 Institute of Applied Mechanics, Friedrich-Alexander Universität Erlangen-Nürnberg…”
Section: Gradient Enhanced Crystal Plasticity In Additive Manufacturiunclassified